2022
DOI: 10.3390/bios12030158
|View full text |Cite
|
Sign up to set email alerts
|

Wafer-Scale LSPR Substrate: Oblique Deposition of Gold on a Patterned Sapphire Substrate

Abstract: Label-free detection of biomolecules using localized surface plasmon resonance (LSPR) substrates is a highly attractive method for point-of-care (POC) testing. One of the remaining challenges to developing LSPR-based POC devices is to fabricate the LSPR substrates with large-scale, reproducible, and high-throughput. Herein, a fabrication strategy for wafer-scale LSPR substrates is demonstrated using reproducible, high-throughput techniques, such as nanoimprint lithography, wet-etching, and thin film deposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…These GLAD-fabricated nanostructures have recently been employed in various biosensing detection settings. Recently, Kim et al reported OAD-based LSPR substrates with a very high throughput by fabricating Au nanostructures (at 45°) over patterned sapphire substrates (PSS) [ 68 ] ( Figure 2 f). Very high LSPR sensitivity was obtained for various biomolecules and bioanalytes.…”
Section: Recent Strategies For Fabrication Of Nanostructures Using Th...mentioning
confidence: 99%
See 1 more Smart Citation
“…These GLAD-fabricated nanostructures have recently been employed in various biosensing detection settings. Recently, Kim et al reported OAD-based LSPR substrates with a very high throughput by fabricating Au nanostructures (at 45°) over patterned sapphire substrates (PSS) [ 68 ] ( Figure 2 f). Very high LSPR sensitivity was obtained for various biomolecules and bioanalytes.…”
Section: Recent Strategies For Fabrication Of Nanostructures Using Th...mentioning
confidence: 99%
“… Different GLAD-structured thin films. ( a ) Slanted-post films; ( b ) zig-zag (chevron) films with 4 arms; ( c ) AgNR/SiO 2 SCL/SiO 2 /PCL/Ag multilayer substrates; ( d ) helical film; ( e ) vertical post structure (reproduced with permission from [ 67 ]); ( f ) 45° tilted top view of Au mushrooms (reproduced with permission from [ 68 ]). …”
Section: Figurementioning
confidence: 99%
“…In various studies, it has been suggested that photon scattering is increased when using patterned sapphire substrate (PSS), resulting in enhanced light extraction [26]. Kim et al utilized wafer-level LSPR substrates by depositing Au films on patterned sapphire substrates and employed the prepared substrates for detecting biomolecules by observing LSPR shifts [27]. However, for 3D substrates such as PSS, a single metal film or particle cannot provide higher Raman enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…In developing LSPR-based POC devices, a key challenge is to produce large-scale LSPR substrates that are reproducible and have high throughput. In a study included in this Special Issue, Kim et al fabricated wafer-scale LSPR substrates using reproducible high-throughput techniques such as nanoimprint lithography, wet etching, and the glancing angle deposition (GLAD) technique [ 28 ]. First, they fabricated hard masks of SiO 2 nanodots on a transparent sapphire wafer using nanoimprint lithography, which was anisotropically etched with a solution of H 2 SO 4 and H 3 PO 4 , resulting in a patterned sapphire substrate (PSS).…”
mentioning
confidence: 99%